ANALISIS PENERAPAN MEDIA PEMBELAJARAN BERBASIS INTERNET MELALUI PEMANFAATAN SMARTPHONE DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (PPKN) DI SMA NEGERI 1 KARTASURA - Subekti, Ila Mursalina, Rusnaini; Muchtarom, Moh. (Prodi PPKn FKIP UNS, 2017)
ABSTRACTThe purpose of this study are, 1) to find out how the internet based- learning media through smartphone use in Pancasila and Civic education learning process at SMAN 1 Kartasura is applied and, 2) to describe the effects of the application of internet based- learning media through smartphone in Pancasila and Civic education learning process at SMAN 1 Kartasura.The approach used in this study was case study with descriptive qualitative method. The data were gained from interviewees, places, events, and documents.Subjects of this study were chosen through purposive sampling technique. The data were collected through interview, observation, and document analysis. In order to gain valid data, validity test was done through data triangulation and method triangulation. While the data were analyzed by using interactive analysis which the steps are as follows: (1) Data Reduction, (2) data exposure (3) Conclusion or verification. The followings are research procedure: (1) Preparation, (2) Data Collection, (3) Data analysis and, (4) research report writing.Based on the result of this study, it could be concluded that: (1) the application of internet based-learning media through smartphone use in Pancasila and Civic education learning process at SMAN 1 Kartasurais a civic teacher? innovation in learning process in accordance with appropriate learning media consideration which is also known as ACTION (Access, Cost, Technology, Interactivity, Organization, and Novelety, but it had not been optimal in access and technology factor. 2) The application of internet based-learning media affect positively to the students? understanding ability. It could be indicated since they had wider knowledge, furthermore they were critical, it was showed when they had courage in expressing their arguments in front of the class. In the other hand, the negative effect of this application was, the students were addicted, interact intensely with their smartphone, and they had to watch inappropriate news or advertisement while accessing the internet. Keywords: Internet based-learning media, Effect, Smartphone